Chain Drill Technique in Teaching Speaking - Dewi Anggraini (Channing : Journal of English Language Education and Literature, 2018)
The objective of the research was to find out whether or not there is a significant difference between the students who are taught by using chain drill technique and the students who are taught by using a conventional technique in teaching students' speaking ability at the seventh-grade students of MTs Nurul Huda Sukaraja. In this research, the writer used an experimental method. The population of this research was 111 students, and there were 48 students was taken by using cluster random sampling for the sample, those were 24 students of experimental group who were taught using chain drill technique and 24 students of the control group who were taught using the conventional technique. For analyzing the data, the writer used the independent t-test, and the result of the calculation showed that t-obtained was higher than t-table (5.73 > 2.0129). It meant that there was a significant difference between experimental and control group. So, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. As a conclusion, using chain drill technique to teach speaking is effective.